(3EOGQI GdYedjGJ GdJShjbjI h fTGWGJgG (B/s - (3GdYdGb, HTjQs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2009)
(3GOGQI YedjGJ GdHjY GdTNUj h fTGWGJg h GOGQI YedjGJ GdJShjb GdOhdj GdGdcJQhfj h fTGWGJgh GOGQI YedjGJ GdJLGQI GdGdjcJQhfjI h fTGWGJgG eY hLhO CSFdI ddefGbTI YfO fgGjI cd aUd(B.s
(3eQGLY U(B.185s
Keywords: (3COGQI GdeHjYGJs; (3GdGOGQIs; (3GdJShjbs